Immuno-informatics aided -design of multi-epitope based vaccine against Nipah henipavirus Glycoprotein G. - Moon, Sabrina Sultana (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Pharmacy, 2021.